Book Review: Exploring the Supply Chain: Theory and Practice - Hafsa Maryam; Dr. Mamun Habib (International Journal of Supply Chain Management, 2013)
This book looks at the basic concepts of Supply Chain Management and provides a comprehensive coverage of the methodology and key strategies drivers in the different processes involved in operating and designing a Supply Chain. It describes the behavioral differences and explains the different tools that have been designed for effective supply chain management. This book is not an academic treatise, though it provides the most comprehensive coverage of the different facets of supply chain management. The authors have made sure that all chapters begin with a small case study that illustrates the specific concepts that are illustrated within the chapter. The book explains the evolution of Supply Chain Management, its concept and philosophy. It also looks at the different elements that go into the design of the Supply Chain and the purchasing functions from the supply chain perspective. The book not only deals with the planning function of SCM, it also covers the fundamentals concepts of forecasting and demand management, planning and control, including the aggregate plan, the different types of inventory models and their classification, work-in-progress and finished goods inventory and quality as a new and major component of Supply Chain Management.